Between Manuscript and Print Transcultural Perspectives, ca. 1400-1800 - Brockstieger, Sylvia; Schweitzer-Martin, Paul (Materiale Textkulturen, 2023)
A cross-cultural, comparative view on the transition from a predominant 'culture of handwriting' to a predominant 'culture of print' in the late medieval and early modern periods is provided here, combining research on Christian and Jewish European book culture with findings on East Asian manuscript and print culture. This approach highlights interactions instead of retracing a linear process from the manuscript book to its printed successor.